Socially Assistive Robots Diffusion in Elderly Care A Pre-Adoption Study by Agent-Based Modeling - Carlotta, Belviso; Rainer, Hasenauer; Bechtold, Ulrike (Journal of Strategic Innovation and Sustainability, 2018)
This paper investigates socially assistive robots’ acceptance and diffusion in eldercare from dependentliving seniors’ perspective by combining data science with the agent-based model of cellular automata able to unveil the emergence of behavioural pattern in a complex system as the result of individual agent interactions. The ratio behind this methodology is that, while social dynamics are often underestimated, they are determinant for the success of an innovation, especially in a pre-market context, in which users do not know the product. In this way, by looking at how opinions are formed and Word of Mouth circulates among social agents, this paper identifies a cluster of enthusiastic seniors, which, if properly addressed, could behave as social hub and influence innovation success. At the same time, however, this work unveils the presence of extreme attitudes and Negative Word of Mouth (NWOM), which, in turn, can lead to innovation rejection.